Lessons in immune adaptations to hypoxia revealed by comparative and evolutionary physiology - Erica C. Heinrich; Michael S. Tift (BMC Biology, 2023)
Recent findings from comparative and evolutionary physiologists reveal novel insights into the regulation of inflammation and immune function under conditions of chronic-sustained and intermittent hypoxia. Comparative approaches provide a valuable gateway for discovering essential principals of physiology and adaptive molecular strategies utilized in nature that protect against clinically relevant stressors, which can guide therapeutic developments in biomedical science.